2009
DOI: 10.1111/j.1945-5100.2009.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

40Ar‐39Ar age determinations of lunar basalt meteorites Asuka 881757, Yamato 793169, Miller Range 05035, La Paz Icefield 02205, Northwest Africa 479, and basaltic breccia Elephant Moraine 96008

Abstract: Ar analyses of several bulk fragments of related meteorites A-881757, Y-793169 and MIL 05035 give crystallization ages of 3.763 ± 0.046 Ga, 3.811 ± 0.098 Ga and 3.845 ± 0.014 Ga, which are comparable with previous age determinations by Sm-Nd, U-Pb Th-Pb, Pb-Pb, and Rb-Sr methods. These three meteorites differ in the degree of secondary 40 Ar loss with Y-793169 showing relatively high Ar loss probably during an impact event ~200 Ma ago, lower Ar loss in MIL 05035 and no loss in A-881757. Bulk and impact melt g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 44 publications
(96 reference statements)
10
54
0
Order By: Relevance
“…The younger Pb-Pb ages of the LaPaz lunar meteorites ($3.0 Ga) are consistent with not only the U-Pb age (2929 ± 150 Ma; Anand et al, 2006) determined in situ from single crystals, but also those determined from the whole rock by Ar-Ar (2985 ± 16 Ma;Fernandes et al, 2009b), Rb-Sr (3020 ± 30 Ma;Nyquist et al, 2005;2990 ± 36 Ma;Rankenburg et al, 2007) and Sm-Nd (2992 ± 170 Ma;Rankenburg et al, 2007) methods. It would be highly unlikely that different dating techniques yield almost identical ages if the system was severely disturbed.…”
Section: Pb-pb Age Of Lap 02224/02205: Implications For Assimilation supporting
confidence: 74%
See 3 more Smart Citations
“…The younger Pb-Pb ages of the LaPaz lunar meteorites ($3.0 Ga) are consistent with not only the U-Pb age (2929 ± 150 Ma; Anand et al, 2006) determined in situ from single crystals, but also those determined from the whole rock by Ar-Ar (2985 ± 16 Ma;Fernandes et al, 2009b), Rb-Sr (3020 ± 30 Ma;Nyquist et al, 2005;2990 ± 36 Ma;Rankenburg et al, 2007) and Sm-Nd (2992 ± 170 Ma;Rankenburg et al, 2007) methods. It would be highly unlikely that different dating techniques yield almost identical ages if the system was severely disturbed.…”
Section: Pb-pb Age Of Lap 02224/02205: Implications For Assimilation supporting
confidence: 74%
“…There are only a few conference abstracts available for its petrology, mineralogy, and geochemistry (Chennaoui and Jambon, 2008;Fernandes et al, 2009a;Jambon and Devidal, 2009;Korotev et al, 2009). The reported crystallization ages for NWA 4734 vary from 2720 ± 40 (Fernandes et al, 2009a) to 3190 ± 190 Ma (2r) (Jambon and Devidal, 2009), the latter being marginally compatible with that of the LaPaz lunar meteorites (Nyquist et al, 2005;Anand et al, 2006;Rankenburg et al, 2007;Fernandes et al, 2009b). To get a deeper understanding of the petrogenesis of NWA 4734 and its implications for lunar magmatism, and to place refined constraints on the genetic relationship between NWA 4734 and the LaPaz lunar meteorites, we have carried out detailed petrological, mineralogical, and geochemical studies on NWA 4734, and made in situ Pb-Pb dating of baddeleyite and zirconolite from NWA 4734 and LAP 02205/02224.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Clasts with a KREEPy basaltic composition have also been reported in the Calcalong Creek meteorite (Hill and Boynton, 2003) and Yamato 983885 (Arai et al, 2005), and several of the basaltic lunar meteorites are reported to have assimilated a KREEP melt component (e.g. NWA 733: Fagan et al, 2003;Jolliff et al, 2003;Borg et al, 2004Borg et al, , 2009, and the LAP clan of lunar meteorites: Zeigler et al, 2005;Anand et al, 2006;Day et al, 2006;Joy et al, 2006;Fernandes et al, 2009, andDhofar 287a: Anand et al, 2003).…”
Section: Nwa 4472 Compared With Other Lunar Meteoritesmentioning
confidence: 88%